Biotoxoid photonic sensors with temperature insensitivity using a cascade of ring resonator and Mach–Zehnder interferometer - Li, Zhenyu (2021)
The great advances in silicon photonic sensing technology have made it an attractive platform for a wide of sensing applications. However, most silicon photonic sensing platforms suffer from high susceptibility to the temperature fluctuation of operating environment. Additional complex and costly chemical signal enhancement strategies are usually required to improve the signal-to-noise ratio (SNR). Here, a biotoxoid photonic sensor that is resistant to temperature fluctuation have been demonstrated. This novel sensor consists of a ring resonator coupled to a Mach-Zehnder interferometer (MZI) readout unit. Instead of using costly wavelength interrogation, our photonic sensor directly measures the light intensity ratio between the two output ports of MZI. The temperature dependence (TD) controlling section of the MZI is used to eliminate the adverse effects of ambient temperature fluctuation. The simulation and experimental results show a linear relationship between the interrogation function and the concentration of analyte under operation conditions. The thermal drift of the proposed sensor is just 0.18%, which is a reduction of 567 folds for chemical sensing and 28 folds for immuno-biosensing compared to conventional single ring resonator. The SNR increases from 6.85 dB to 19.88 dB within a 2°C temperature variation. The high SNR optical sensor promises great potential for amplification-free of detection of nucleic acids and other biomarkers.